2017
DOI: 10.1101/126771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Akt regulation of glycolysis mediates bioenergetic stability in epithelial cells

Abstract: 10Cells use multiple feedback controls to regulate metabolism in response to nutrient and signaling 11 inputs. However, feedback creates the potential for unstable network responses. We examined how 12 concentrations of key metabolites and signaling pathways interact to maintain homeostasis in 13 proliferating human cells, using fluorescent reporters for AMPK activity, Akt activity, and cytosolic 14

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…We were therefore interested if a distinct metabolic profile of the leukemic cells would be associated with a different prerequisite activity of the signaling pathways. Indeed, we found a profound difference in p-AKT and c-MYC, the regulators of glycolysis [21,22], between T-and B-ALL cells and decreased level of p-GSK3b in B-ALL cell lines. In the case of the AML cell lines, the proteins S6 and p-S6 were more expressed than in ALL cells.…”
Section: Discussionmentioning
confidence: 75%
“…We were therefore interested if a distinct metabolic profile of the leukemic cells would be associated with a different prerequisite activity of the signaling pathways. Indeed, we found a profound difference in p-AKT and c-MYC, the regulators of glycolysis [21,22], between T-and B-ALL cells and decreased level of p-GSK3b in B-ALL cell lines. In the case of the AML cell lines, the proteins S6 and p-S6 were more expressed than in ALL cells.…”
Section: Discussionmentioning
confidence: 75%
“…This inhibition might result from the glutamate-induced decrease in [Mg 2+ ] i demonstrated in this study ( Figure 2 and Figure 3 ). The fact that the Akt/mTOR signal is also involved in regulation of both cellular ATP synthesis and also apoptotic signals [ 35 , 46 , 47 ] would explain why maintaining a high [Mg 2+ ] i prevent neuronal cell death. In this study, we showed that inhibition of mTOR abolished the attenuation of glutamate excitotoxicity by inhibiting Mg 2+ extrusion ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these interactions have not been yet observed in matrix-deprivation conditions. Such context-specific differences may allow for other dynamics for AMPK and Akt, such as oscillations seen in MCF10A cells upon inhibition of glycolysis and mitochondrial ATPase [65]. Intriguingly, AMPK can form double negative feedback loops with other molecules such as mTORC1 [66], which is involved in a similar feedback loop with ULK1 [67].…”
Section: Discussionmentioning
confidence: 99%